MILITARY RULE WITHIN THE FRAMEWORK OF A DEMOCRATIC SYSTEM: THE GAMBIA’S EXPERIENCE OF COMBINING THE INCOMPATIBLES UNDER THE AFPRC/ APRC ADMINISTRATIONS (1994-2017) - ABOUBACAR ABDULLAH SENGHORE (International Studies Journal)
This article examines the challenges of Military Rule within the structure of a Democratic system of Governance and the ensuing contradictions of this combination focusing mainly on The Gambia experience with the AFPRC/APRC administrations from 1994-2017). It has interrogated the nature of the systemic contradictions between military rule and democratic governance as experienced in The Gambia since the 1994 military takeover which paved the way to the arrival, in 1997, of the second republic, and the implications of this contradiction owing mainly to the military style of governance and management in general and The Gambia experience in particular. Under the period of study there were a lot democratic contractions and incompatibles that played out in The Gambia Second Republic that tagged the country as a country with democratic concerns. Using mainly secondary sources and insider experience; being a Minister under the regime of investigation the research was analyses. The findings of the research show that the regime was authoritarian in their style of governing and also that their regime systematically targeted political opponents – subjecting them to torture, extrajudicial execution, arbitrary arrests and detention and enforced disappearances. They accused the military government of serious human rights violations, abuse of rule of law, suppression of the Media, frequent and irrational hiring and firing of judges and top civil servants. The article submitted that there is a marked difference between civil and military leaders in their leadership and management styles in conducting the affairs of the nation. Military rule is autocratic in nature whilst civilian rule is consultative in nature and humanely rational in approach. Thus, and as observed below the military-led administration in The Gambia has not done better in terms of respecting and maintaining rule of law and respecting fundamental human rights, which put a big question mark (?) on the democratic ethos and credentials of military regime in The Gambia.